2007
DOI: 10.1530/rep-06-0048
|View full text |Cite
|
Sign up to set email alerts
|

Delayed and stage specific phosphorylation of H2AX during preimplantation development of γ-irradiated mouse embryos

Abstract: Within minutes of the induction of DNA double-strand breaks in somatic cells, histone H2AX becomes phosphorylated in the serine 139 residue at the damage site. The phosphorylated H2AX, designated as g-H2AX, is visible as nuclear foci in the irradiated cells which are thought to serve as a platform for the assembly of proteins involved in checkpoint response and DNA repair. It is known that early stage mammalian embryos are highly sensitive to radiation but the mechanism of radiosensitivity is not well understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 37 publications
2
40
1
1
Order By: Relevance
“…Interestingly, they document a different degree of H2A.X phosphorylation responsiveness to DNA damage between male and female chromatin, in line with our observations. Our work contrasts to a report published earlier by Adiga et al, where basal levels of γH2A.X are undetectable in normal embryos (Adiga et al, 2007). This is very likely due to different immunostaining protocols and techniques (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, they document a different degree of H2A.X phosphorylation responsiveness to DNA damage between male and female chromatin, in line with our observations. Our work contrasts to a report published earlier by Adiga et al, where basal levels of γH2A.X are undetectable in normal embryos (Adiga et al, 2007). This is very likely due to different immunostaining protocols and techniques (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been shown that radiation-induced chromosome instability in vitro could be attributed to the long-term delay in chromosome replication (13). It is also suggested that one of the initial steps of damage response is inefficient in early preimplantation stages of mouse embryos because of altered chromatin conformation at these stages (7), and these could be the possible reasons for delayed onset of genetic instability in preimplantation embryos derived from the DNA damaged sperm.…”
Section: Discussionmentioning
confidence: 99%
“…Although embryos do show some DNA repair capacity (7), the level of DNA damage that embryos tolerate during their development is not clear (8). It has been shown that the zygotic stage of mouse embryogenesis lacks G1/S arrest because fertilization of DNA-damaged sperm does not delay the entry of the zygotes to S-phase, although DNA synthesis in such embryos was severely suppressed (2).…”
mentioning
confidence: 99%
“…In the present study, while developmental abnormalities were observed on day 2.0 onwards, it was marked after day 3.0, which corresponds to the morula blastocyst transition stage. Hence, the embryonic response to genetic insult introduced by the sperm is stage specific, which is possibly associated with changes in chromatin conformation or activation of the embryonic genome (22). Further studies are required to elucidate the mechanism associated with sperm DNA damage response during embryonic genome activation.…”
Section: Discussionmentioning
confidence: 99%